Lippincott's illustrated reviews biochemistry - Abali, Emine Ercikan; Cline, Susan D.; Franklin, David S.; Viselli, Susan (Lippincott illustrated reviews, 2022)
"Biochemistry is the study of how our bodies utilize the nutritional substances in our diet to make building blocks, fuels, and communication molecules for our cells. It also includes the processes by which we convert chemicals within our bodies and eliminate chemicals from our bodies"